Kultura zaufania w relacji firma – pracownik - Młokosiewicz, Marta (Annales. Etyka w Życiu Gospodarczym, 2015)
A culture of trust leads to better use of knowledge and human skills, so important in an economy based on knowledge, innovation and change. Polish society is characterized by a culture of distrust, and this atmosphere translates into interpersonal relationships in companies. The challenge is therefore to recognize the conditions for building and strengthening organizational trust. Trust is related to personal reliability, which means respecting moral norms and the rights of others. Focusing on the company-employee relationship, in this paper the author has set herself the goal of recognising how – in the context of ethical standards – the culture of trust is shaped in companies in Poland. The introductory – theoretical – part of the study looks at the role of trust in the functioning of an organization. The empirical part includes the available research on moral standards and trust in Polish enterprises. The summary points to the conclusions of the analysis undertaken.